mpact of cyclophosphamide and fluconazole on hair cycle in a rodent model – the problem of drug-induced alopecia - Latusek, Małgorzata; Brzezińska-Wcisło, Ligia (Dermatology Review/Przegląd Dermatologiczny, 2013)
Introduction . Adverse drug reactions play an important role. Often they are severe, involve many organs and determine the further treatment. One of them is drug-induced alopecia. The mechanism of this side effect is still unknown and evidence of drug toxicity is not always proven. The frequency of drug-induced alopecia in humans is not known. Objective. To assess whether cyclophosphamide and fluconazole induce changes in the hair cycle in a rodent model. Material and methods. Male Wistar rats were divided into equal groups. Rats in the first group (K1) were receiving distilled water. Rats in the experimental groups (G1, G2) were receiving via a gastric tube selected drugs dissolved in distilled water. Twice a week macroscopic examination was performed, followed by microscopic examination of hair to assess shaft and root abnormalities. Anagen, catagen, telogen and pathologic types of hair were counted. Depending on telogen count and dystrophic hair appearance the type of hair loss was established. In addition some laboratory tests were performed. Results . Cyclophosphamide increased the telogen and dystrophic count and induced the premature catagen phase in every cycle. Fluconazole also induced premature catagen involution and increased the telogen count. Conclusions . Cyclophosphamide and fluconazole have an influence on the hair cycle. Each drug triggers a different type of alopecia and its course depends on the time of drug exposure.